NLRC5 interacts with RIG‐I to induce a robust antiviral response against influenza virus infection. Issue 3 (23rd December 2014) - Ranjan, Priya; Singh, Neetu; Kumar, Amrita; Neerincx, Andreas; Kremmer, Elisabeth; Cao, Weiping; Davis, William G.; Katz, Jacqueline M.; Gangappa, Shivaprakash; Lin, Rongtuan; Kufer, Thomas A.; Sambhara, Suryaprakash
<x xml:space="preserve">Abstract</x> The NLR protein, NLRC5 is an important regulator of MHC class I gene expression, however, the role of NLRC5 in other innate immune responses is less well defined. In the present study, we report that NLRC5 binds RIG‐I and that this interaction is critical for robust antiviral responses against influenza virus. Overexpression of NLRC5 in the human lung epithelial cell line, A549, and normal human bronchial epithelial cells resulted in impaired replication of influenza virus A/Puerto Rico/8/34 virus (PR8) and enhanced IFN‐β expression. Influenza virus leads to induction of IFN‐β that drives RIG‐I and NLRC5 expression in host cells. Our results suggest that NLRC5 extends and stabilizes influenza virus induced RIG‐I expression and delays expression of the viral inhibitor protein NS1. We show that NS1 binds to NLRC5 to suppress its function. Interaction domain mapping revealed that NLRC5 interacts with RIG‐I via its N‐terminal death domain and that NLRC5 enhanced antiviral activity in an leucine‐rich repeat domain independent manner. Taken together, our findings identify a novel role for NLRC5 in RIG‐I‐mediated antiviral host responses against influenza virus infection, distinguished from the role of NLRC5 in MHC class I gene regulation.